2019
DOI: 10.1021/acs.joc.9b02427
|View full text |Cite
|
Sign up to set email alerts
|

Nitroacetic Esters in the Regioselective Synthesis of Isoxazole-3,5-dicarboxylic Acid Derivatives

Abstract: An efficient and high-yielding strategy to prepare “unsymmetrical” 4-aryl-isoxazol-3,5-dicarboxylic acid derivatives from nitroacetic esters and aromatic aldehydes has been developed. The strategy is based on the isolation and usage of the previously missed intermediate of the Dornow reaction5-hydroxy-6-oxo-4-aryl-6H-1,2-oxazine-3-carboxylates. In addition, the mechanism of the Dornow reaction was partially revised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…A well‐organized and good yield‐producing approach to formulate “unsymmetrical” 4‐aryl‐isoxazole‐3,5‐monocarboxylic acid ( 4 , 6 , 7 , 9 – 16 ) and 4‐aryl‐isoxazole‐3,5‐dicarboxylic acid (8) analogues by nitroacetic esters 1 with aromatic aldehydes 2 reported (Scheme 39) [60].…”
Section: Synthetic Methods Of Isoxazole and Their Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…A well‐organized and good yield‐producing approach to formulate “unsymmetrical” 4‐aryl‐isoxazole‐3,5‐monocarboxylic acid ( 4 , 6 , 7 , 9 – 16 ) and 4‐aryl‐isoxazole‐3,5‐dicarboxylic acid (8) analogues by nitroacetic esters 1 with aromatic aldehydes 2 reported (Scheme 39) [60].…”
Section: Synthetic Methods Of Isoxazole and Their Derivativesmentioning
confidence: 99%
“…The [2 + 2 + 1] cycloaddition reaction route mediated by copper nitrate was utilized to create a series of S C H E M E 3 9 Synthesis of "unsymmetrical" 4-aryl-isoxazol-3,5-dicarboxylic acid derivatives [60] isoxazole and isoxazoline analogues. The reaction of fluoraldehyde 1 and different aryl-carboxylic acid 2 as the starting precursor yielded 3-aryl isooxazoline 3, which then further treatment substituted aryl enones 4 produces different substituted isoxazoles 5.…”
Section: Other Synthetic Routesmentioning
confidence: 99%
“…A recent re-examination of the process 79 has shown that dinitroglutarate, under appropriate reaction conditions, undergoes a different ring-closure to oxazinones 34 (Scheme 18) and a general synthesis of these compounds is reported from nitroacetic esters and aromatic aldehydes ( 1 , R = Ar) in acetonitrile and Et 2 NH (Baranov and his co-workers). 79,80…”
Section: Regioisomerismmentioning
confidence: 99%
“…Thus, the regioselective preparation of 4-arylisoxazole-3,5-dicarboxylic acid derivatives 35 is described, including ester (Me, Et, and i-Pr) at C-3 with amide at C-5 (over 60 examples) and unsymmetrical diamides (2 examples) (Scheme 19). 80…”
Section: Regioisomerismmentioning
confidence: 99%
“…Subsequently, intermediates 111 were reacted with various functionalized amines in the presence of chloroform at 70 °C for 12 h, which furnished the 3,4,5-trisubstituted isoxazole derivatives 112 ( Scheme 27 ). 39 …”
Section: Metal-free Synthesis Of Isoxazoles Via Mi...mentioning
confidence: 99%